Microbial diversity in an Oxisol under no-tillage and conventional tillage in southern Brazil - Babujia, Letícia; Silva, Adriana; Nogueira, Marco; Hungria, Mariangela (Revista Ciência Agronômica, 2014)
The no-tillage (NT) system of soil management is recognized as more sustainable than conventional tillage (CT), with an important role played by soil microorganisms. The objective of this study was to estimate differences in soil microbial diversity under NT and CT at different soil depths. For that, bacterial (16S rDNA) and fungal (18S rDNA) communities were evaluated by denaturing gradient gel electrophoresis (DGGE) in a 20-year field experiment established on an Oxisol in southern Brazil on which soybean has been grown in the summer and wheat in the winter. Soil samples were collected at the depths of 0-5, 5-10, 10-20 and 20-30 cm, and submitted to DGGE analyses. The results revealed lower similarity (28%) between bacterial communities in the NT and the CT systems at the 0-5 cm layer. The Shannon index (H) confirmed higher bacterial diversity with NT at all depths, when compared to CT. In relation to fungal communities, higher diversity was detected with CT, especially at the 0–5-cm depth. The results indicate that fungal communities can be more tolerant to environmental stresses related to soil disturbance than bacteria. More emphasis should be given for understanding processes affecting the diversity of microorganisms in agricultural soils, with particular emphasis on tillage systems.